Aceh sebagai Wilayah Terkuat yang Sulit Dijajah Belanda - sari, Windi sekar (Historia Madania: Jurnal Ilmu Sejarah, 2022)
This article describes the greatness of Aceh as the strongest region that is difficult to colonize by the Dutch. The Dutch colonization itself only emerged in Aceh around the end of the 19th century AD. Aceh is the capital of the Indonesian nation's struggle. The method used in this article is a historical method that uses a variety of literature on the problems presented, relating to the history of Aceh and the Dutch colonialists. The contents of the article provide an explanation of the Dutch journey which was not easy to just colonize the Aceh region. Likewise, the people of Aceh are not easily influenced by the cunning Dutch way. So in this article, we will discuss the strength and form of Aceh's defense, starting with the political steps of the Acehnese government against the Dutch, the Acehnese people's struggle to defend their beloved homeland because the Acehnese people considered the Dutch colonials to be infidels who had to be fought, they named the war. with the war fii sabilillah (jihad in the way of Allah). Which then made Aceh the last area to be colonized by the Dutch, which was about Â± 30 years. Â  Keywords: Dutch Colonial, Aceh War, Aceh People.